On the finite Loop Algebra of the smallest Moufang loop M(S_3,2) - Sidana, Swati; Sharma, R. K. (Armenian Journal of Mathematics, 2016)
Let F[L] be a loop algebra of a loop L over a field F. In this paper, we obtain the unit loop of the loop algebra F[L], where L is the smallest Moufang loop M(S_3,2) and F is a finite field of characteristic different from 3.